2011
DOI: 10.1007/s12253-011-9417-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Topoisomerase II Alpha Protein Expression and Outcome After Adjuvant Dose-Dense Anthracycline-Based Chemotherapy

Abstract: There is a need for the selection of those breast cancers where benefit may be attained from the addition of an anthracycline to the adjuvant chemotherapy. The expression of topoisomerase II alpha (TOP2A) protein in 3 cohorts of breast cancers treated with adjuvant dose-dense anthracycline-based chemotherapy was determined retrospectively. The TOP2A status was analysed in relation with the other standard tumour features and the outcome. TOP2A IHC results were assessable in 106 patients: with a cut-off value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In consistent with previous studies [ 30 , 31 , 34 ], we found TOP2A protein was significantly associated with high tumor grade and Ki67 index, suggesting that tumors with high level of TOP2A expression were more aggressive. No association between TOP2A expression and age, menstrual status, tumor size, lymph node status, pathological type were observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In consistent with previous studies [ 30 , 31 , 34 ], we found TOP2A protein was significantly associated with high tumor grade and Ki67 index, suggesting that tumors with high level of TOP2A expression were more aggressive. No association between TOP2A expression and age, menstrual status, tumor size, lymph node status, pathological type were observed.…”
Section: Discussionsupporting
confidence: 93%
“…However, no standard antibodies, staining procedure, and scoring system have been recommended. Various cut-off values such as 5% [ 29 ], 10% [ 30 ], 15% [ 31 ], 20% [ 26 ], and 30% [ 32 ] have been applied in different studies. Other studies took both the staining intensity and percentage of positive cells into consideration to defined TOP2A status [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These indicators, although well established, are all related to tumor aggressiveness. Recent evidence has shown that proliferation markers, such as Ki-67 and proliferating cell nuclear antigen (PCNA), may have independent prognostic value [13]. Although these proliferation markers have potential, recent studies indicate that thymidine kinase 1 (TK1), another marker associated with proliferation, may be a better prognostic marker than either Ki-67 or PCNA [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with TOP2A-positive breast cancer are more sensitive to anthracyclines than TOP2A-negative patients [38]. TOP2A is highly expressed in more advanced uterine leiomyosarcoma with a high mitotic index but not in nonmalignant uterine diseases [39].…”
Section: B C Dmentioning
confidence: 99%